Application of a screening method for fentanyl and its analogues using UHPLC‐QTOF‐MS with data‐independent acquisition (DIA) in MSE mode and retrospective analysis of authentic forensic blood samples. Issue 4 (27th October 2017) - Noble, Carolina; Weihe Dalsgaard, Petur; Stybe Johansen, Sys; Linnet, Kristian
Abstract: The steady appearance of new fentanyl analogues and the associated overdose deaths require the development of sensitive screening approaches to detect these compounds in biological samples and seizures. We developed a targeted screening method to detect 50 4‐anilidopiperidine‐related fentanyl analogues in whole blood using ultra‐high performance liquid chromatography quadrupole time‐of‐flight mass spectrometry in data‐independent acquisition mode. Sample preparation was performed using protein precipitation on a fully automated robotic setup. Thirteen analogues were selected to validate the method. A small matrix ion enhancement effect (110–123%) was observed for all of the compounds; the recovery ranged from 67% to 81% and the process efficiency from 81% to 98%. Limit of detection was within 0.0005–0.001 mg/kg and limit of identification ranged from 0.001 to 0.005 mg/kg. In the retrospective analysis of 2339 forensic blood samples, the major finding was fentanyl ( n  = 56), followed by alfentanil (n = 5) and remifentanil ( n  = 1). Identification of 34 fentanyl analogues was based on the predicted product ions resulting from common fentanyl‐specific collision‐induced cleavages, particularly on the product ion result of the fragmentation on the C‐N bond between the phenylamide moiety and the piperidine ring. The proposed hypothesis was supported by the targeted analysis of 16 fentanyl analogues using this method and available published mass spectral data sources for fentanyl analogues. A targeted screening method for 50 fentanyl analogues was successfully validated and implemented to analyse authentic blood samples, where identifying targeted fentanyl analogues was tentatively achieved without using reference standards. Abstract : The number of fentanyl and fentanyl analogues‐related overdose deaths and acute intoxications has grown dramatically worldwide during the last years. We utilized a screening method using high resolution mass spectrometry in MS E mode to identify 50 fentanyl analogues. We observed that along all fentanyl analogues with a 4‐anilidopiperidine core there is a class‐specific collision‐induced cleavage useful for their tentative identification without using reference standards. Furthermore, the presented method creates the possibility of screening for new synthetic 4‐anilidopiperidine fentanyl analogues.